Caracterización morfológica de las malezas del género Echinochloa - Amat Jiménez, Pedro Javier (2022)
Plants of this genus Echinochloa show very varied characteristics and their taxonomy is confusing. The most cosmopolitan and economically important weedy species of the genus Echinochloa are: Echinochloa crus-galli (L.) Beauv. and Echinochloa colona, both species occur in temperate to tropical regions in the world. They possess all the aggressive traits and adaptive capabilities necessary to survive and successfully oppose a selection of geographic and climatic conditions. They are fast-day C4 annual tropical weeds, with a tendency to grow in intense climates. These weeds adapt to numerous levels of temperature and humidity to complete their life cycle. The morphological, physiological and biochemical composition of these weeds allows them to become a robust competitor to rice and other crops. E. crus-galli and E. colona can produce an enormous amount of seeds and still have a level of seed dormancy, which guarantees their propagation, as well as the accumulation of seed banks within the soil profile. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the morphological characterization of the weeds of the genus Echinochloa. From the above, it was determined that the most cosmopolitan and economically important weed species of the genus Echinochloa are: Echinochloa crus-galli (L.) Beauv. and Echinochloa colona, which can reduce crop yields up to 79%, due to direct competition for nutrients, water, light and space. For the management of weed species of the genus Echinochloa spp. there are several alternatives such as cultural practices that favor the management and control of Echinochloa spp. In the weed species E. crus-galli and E. colona, populations with resistance to ACCase inhibitor herbicides have been identified due to a mutation within the site of action of the herbicide movement.